Low- pT e+e- Pair Production in Au +Au Collisions at sNN =200 GeV and U + U Collisions at sNN =193 GeV at STAR - STAR Collaboration (Physical Review Letters, 2018)
We report first measurements of e+e- pair production in the mass region 0.4<Mee<2.6 GeV/c2 at low transverse momentum (pT<0.15 GeV/c) in noncentral Au+Au collisions at sNN=200 GeV and U+U collisions at sNN=193 GeV. Significant enhancement factors, expressed as ratios of data over known hadronic contributions, are observed in the 40%-80% centrality of these collisions. The excess yields peak distinctly at low pT with a width (âpT2â ©) between 40 and 60 MeV/c. The absolute cross section of the excess depends weakly on centrality, while those from a theoretical model calculation incorporating an in-medium broadened ρ spectral function and radiation from a quark gluon plasma or hadronic cocktail contributions increase dramatically with an increasing number of participant nucleons. Model calculations of photon-photon interactions generated by the initial projectile and target nuclei describe the observed excess yields but fail to reproduce the pT2 distributions. © 2018 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the »https://creativecommons.org/licenses/by/4.0/» Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI. Funded by SCOAP3.
52 citations (Crossref) [2023-10-31]
Keywords: Au+Au collisions; Colliding beam accelerators; Enhancement factor; Germanium compounds; Gold; Mass regions; Measurements of; Pair production; Photons; Transverse momenta; dept.phy; peer-reviewed